1993
DOI: 10.1093/tropej/39.1.16
|View full text |Cite
|
Sign up to set email alerts
|

II. Evaluation of the Impact on Growth of a Controlled 6-month Feeding Trial on Children (6-24 Months) Fed a Complementary Feed of a High Energy-Low Bulk Gruel Versus a High Energy-High Bulk Gruel in Addition to Their Habitual Home Diet

Abstract: Twenty-one pairs of slum children (6-24 months) were pair-matched for age and weight. The experimental group consumed a complementary feed of a high energy (1.63 Kcal/ml), but low bulk wheat gruel providing a mean 199 Kcal/child/day v. the control group which consumed an identical (1.63 Kcal/ml), but high bulk gruel providing a mean 50 Kcal/child/day for a period of 180 days. The home diet (breastmilk+family diet) provided about 470 Kcal/child/day in both groups. A comparative evaluation of growth at commencem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
3

Year Published

1994
1994
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
0
12
0
3
Order By: Relevance
“…The etiologies of these conditions are multi-factorial and are often attributed to poor maternal nutritional, poor access to healthcare and low birth weight. Adequate feeding, however, can lead to catch-up growth, which negates some of these adverse influences 20 – 22. Our analyses show that a substantial proportion of the population is still underweight even during school years and adolescence in Pakistan.…”
Section: Discussionmentioning
confidence: 75%
“…The etiologies of these conditions are multi-factorial and are often attributed to poor maternal nutritional, poor access to healthcare and low birth weight. Adequate feeding, however, can lead to catch-up growth, which negates some of these adverse influences 20 – 22. Our analyses show that a substantial proportion of the population is still underweight even during school years and adolescence in Pakistan.…”
Section: Discussionmentioning
confidence: 75%
“…It acts by activating amylase and phytase enzymes which break the starch down into sugars and reduce the phytate content, leading to a more liquid porridge of lower viscosity and greater palatability. This resulted in 30–40% increases in energy intake in studies from Bangladesh,21India,7 and Tanzania 22. Although a Jamaican study did not find much increase in mean energy intake on α-amylase ‘thinned’ maize porridge,23 it did halve mean feeding times, which would have led to bigger differences in intake in a setting where feeds are less well supervised than in a research unit.…”
Section: Discussionmentioning
confidence: 99%
“…Although in some instances this may be because of limited household food availability, in many cases other factors, such as the health status of the child (2,3) and the characteristics of the diet (4), may be the primary influences on energy consumption. Several authors have reported, for example, that the high viscosity of high-energy-density, starch-containing porridges limits the amount that can be consumed (5)(6)(7)(8)(9), although others have found no benefit to liquefaction of these foods (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%